Desenvolvimento profissional de uma professora alfabetizadora : a construção de práticas bem-sucedidas - Oja, Aline Juliana (2011)
Faced with an educational overview that reveals, in many instances, school failure through poor outcomes related to public education, the present research seeks to enrich the analysis of elements related to the teaching work from the understanding of a pedagogical practice that promotes the achievement of students in the initial stage of schooling. In this sense, the research was guided from the following question: How does a literacy teacher considered successful build its daily practice? To answer this question, it was defined as the main objective to describe and analyze the professional development of a literacy teacher considered successful and the building of its everyday teaching practices. Considering these aspects, we chose to develop a qualitative approach, and as instruments of data collection it was used participant observation and semi-structured interview, plus the contribution of the approach that deals with the teacher s life story. The choice of a literacy teacher considered successful was made from a process of reflection and research, and the criteria for defining the research subject was based on prior knowledge of the researcher, official information provided by the State Department of Education - São Paulo, related to student achievement in the evaluation of SARESP2, by appointing the director and also by the recognition among their pairs. The research took place in the second year s class of the chosen teacher, situated in a public school in São Paulo. Seeking to contextualize the questions raised by this study, we used the theoretical contributions of several authors on the current landscape of research on teaching, relating it to the conception that teachers construct knowledge about their work and that recognition of this perspective indicates progress toward overcoming the dilemmas arising from the complexity of the teaching profession. It was also proposed some reflections on the landscape of the researches that deal with literacy, in particular successful practices, also exploring issues about the literacy teacher education. Furthermore, it approaches the subject of methods used in working with literacy, clarifying issues surrounding the constructivist approach in this context. The data from the analysis were grouped into two dimensions: the story of life and training and literacy practices. Based on the results of that work, it is concluded that the study of teacher knowledge, knowledge base and professional development of teachers enables the clarification of the experiences built throughout the history of training and in everyday classroom are rich source of practical knowledge, teachers resulting from reflections on several occasions made available by the educational intervention, both at school and elsewhere. The successful practices constructed by the teacher investigated are the result of a complex process of development and professional performance that reflects a mix of objective questions (classroom, teaching resources, physical space, among others) and subjective explained by personal characteristics and training of teaching throughout the analysis presented here. In fact, although the context and external factors may influence the learning process, the results show that the practices of literacy are crucial for students to be encouraged, and achieve success in reading and writing, even though each take ownership of knowledge in unique ways.